2021
DOI: 10.1021/acs.joc.0c03026
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxidative Regioselective C–H Cyanation of Imidazo[1,2-a]pyridines

Abstract: Electrochemical oxidative regioselective C−H cyanation of imidazo[1,2-a]pyridines was developed using readily available TMSCN as the cyano source. The KH 2 PO 4 /K 2 HPO 4 buffer was essential for this transformation. This protocol was compatible with a broad range of substituted imidazo[1,2a]pyridines and provided the C3 cyanated products in moderate to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Finding an efficient and practical method for cyanation of more complex heterocycle, e. g., imidazopyridine is even more difficult work. Liu and Sun et al [19] . very recently (in 2021) reported an electrochemical oxidative C−H cyanation of imidazopyridines 1 using TMSCN 13 as the cyano source to synthesize C‐3 cyanated products 14 (Scheme 7).…”
Section: Electrochemical Functionalization Of Imidazopyridinementioning
confidence: 99%
“…Finding an efficient and practical method for cyanation of more complex heterocycle, e. g., imidazopyridine is even more difficult work. Liu and Sun et al [19] . very recently (in 2021) reported an electrochemical oxidative C−H cyanation of imidazopyridines 1 using TMSCN 13 as the cyano source to synthesize C‐3 cyanated products 14 (Scheme 7).…”
Section: Electrochemical Functionalization Of Imidazopyridinementioning
confidence: 99%
“…[33] Regioselective C-3 cyanation of imidazo[1,2-a] pyridine core is reported previously. [34] However, directed cyanation at ortho position of 2-arylimidazo[1,2-a]pyridine is rare. Song & Hao et al [35] first reported ortho biscyanation of 2-arylimidazo[1,2-a]pyridines (24 a) assisted by N-directed ortho double CÀ H activation using N-cyano-N-phenylp-methylbenzenesulfonamide (NCTS) (24 b) as a cyanating agent.…”
Section: Cyanationmentioning
confidence: 99%
“…Using N -hydroxybenzimidoyl chloride ester (NHBC) to activate amino acids, Wang et al enabled a leaving-group-assisted decarboxylative coupling of amino acids with heteroarenes (Scheme c). In continuation of our study on the direct C–H functionalization of heteroarenes, we herein disclose the aminoalkylation of quinoxalinones and some other heterocycles by the decarboxylative coupling of α-amino acids under photoredox conditions in air (Scheme d).…”
mentioning
confidence: 93%